A Comprehensive Review of Classical and Modern Statistical Methods in Research - Bele, Charudatta Dattatraya (AG Volumes, 2025)
Studies are significantly influenced by research methodologies. Quantitative research necessitates the utilisation of statistical methodologies. Advanced statistical analysis is essential to contemporary research in a number of fields, such as engineering, economics, social sciences, and healthcare. The literature on both traditional and contemporary statistical research methodologies is reviewed in this article. This review highlight that statistical methods remain foundational to research, evolving significantly with advancements in technology and data science. While classical techniques still hold value, the rise of big data, machine learning, Bayesian methods, and network analysis demands modern, adaptive approaches. The integration of statistical software such as SPSS, R, MATLAB, and Excel has revolutionized data analysis, making it more efficient and accessible. Researchers must carefully select software based on application needs to ensure accurate and meaningful results. As the digital age advances, understanding and applying both traditional and modern statistical methods is essential for reliable, insightful, and impactful research across disciplines.